2023
DOI: 10.1186/s12974-023-02856-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of non-coding RNAs in neuroinflammation mediated by microglia and astrocytes

Abstract: Neuroinflammation has been implicated in the initiation and progression of several central nervous system (CNS) disorders, including Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, multiple sclerosis, ischemic stroke, traumatic brain injury, spinal cord injury, viral encephalitis, and bacterial encephalitis. Microglia and astrocytes are essential in neural development, maintenance of synaptic connections, and homeostasis in a healthy brain. The activation of astrocytes and microglia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 210 publications
0
8
0
Order By: Relevance
“…and found that levels of VEGF-C were moderately elevated ( Figures 2A-C ). Microglia and astrocyte also play important roles in inflammation and neurological disorders, as their activation and release of inflammatory mediators can influence disease progression ( 26 ). Subsequently, we traced the source of VEGF-C and explored its connection with microglia and astrocyte.…”
Section: Resultsmentioning
confidence: 99%
“…and found that levels of VEGF-C were moderately elevated ( Figures 2A-C ). Microglia and astrocyte also play important roles in inflammation and neurological disorders, as their activation and release of inflammatory mediators can influence disease progression ( 26 ). Subsequently, we traced the source of VEGF-C and explored its connection with microglia and astrocyte.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, microglial proliferation and activation within the brain, particularly around Aβ plaques, are prominent characteristics of AD [ 24 ]. Astrocytes contribute directly to neuroinflammatory and neurodegenerative processes in AD [ 61 ], and lncRNAs mediate neuroinflammation in glial cells [ 62 ]. For example, MEG3 overexpression has been reported to inhibit astrocyte activation, reduce inflammatory injury, and alleviate neuronal damage [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous ~ 22 nt RNAs targeting mRNAs for cleavage or translational repression, which played a regulatory role in the immunity process, particularly in BBB and CNS inflammatory reaction [ 39 , 40 ]. For instance, miR-17-5p mediated leukemia inhibitory factor modulation of reactive astrocyte proliferation [ 41 ], and astrocytic miR-19b-3p participated in promoting the production of inflammatory cytokines in JEV infection [ 42 ].…”
Section: Discussionmentioning
confidence: 99%